‘SINGWANG STRIKE-SLIP DUPLEX’ AROUND THE POHANG BASIN, SE KOREA: ITS STRUCTURAL EVOLUTION AND ROLE IN OPENING AND FILL OF THE MIOCENE BASIN - Choi P. (My University, 2006)
In order to elucidate the structural characteristics of the Yangsan Fault in southeastern Korea the Ganggu-Angang area has been studied in terms of fault branching and fault linkages. According to the results of this study, eight faults (e.g., the Winmal, Docheon, Yugye, Gojusan, Naengsu, Malgol, Ogeum and Moa faults) branch from the Yangsan Fault, and divide it into at least nine segments. The strike separations of these faults suggest that they are much longer than their presently exposed lengths and that the majority of them are linked to the Jangsa Fault as connecting faults. This distribution of faults comprises the ‘Sing-wang strike-slip duplex’ with the geometry of an extensional strikeslip duplex or pull-apart basin. Block faulting took place along the connecting faults and related transfer faults, resulting in the deposition of coarse grained sediments in fan-delta systems. The shape of basalt masses around the northern tip of Yangsan Fault reveals that this fault had a sinistral motion, possibly in relation to the Pliocene (?) rotation of the Pohang-Ulsan Block. At a recent stage, the Yangsan Fault was displaced by WNW-ESE, E-W or ENE-WSW trending faults. Quaternary reactivation occurred along the Yangsan Fault but not along the Jangsa Fault.
Keywords: YANGSAN FAULT; JANGSA FAULT; CONNEETING FAULT; SINGWANG STRIKE-SLIP DUPLEX; POHANG BASIN; SEGMENT; Quaternary; Pliocene; Cenozoic::Quaternary; Кайнозой::Четвертичная; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен